Adult Manifestation of Lower Urinary Tract Dysfunction as Daytime Urinary Incontinence and Nocturnal Enuresis in a Case With Spinal Lipoma - Taiju Hyuga; Koki Sugimura; Kimihiko Moriya (IJU Case Reports)
ABSTRACT Introduction Generally, lower urinary tract function is considered to show few changes in adulthood for cases of spina bifida. Case Presentation The case involved a 33‐year‐old man with a primary diagnosis of spinal lipoma. Urological management by spontaneous voiding was maintained, and uroflowmetry at 23 years old showed a maximum flow rate of 9.6 mL/s and a residual urine volume of 35 mL; then urological follow‐up was ended. The patient developed nocturnal enuresis and daytime urinary incontinence. Residual urine was exceeding 500 mL. Bladder deformity was identified on VCUG. UDS showed a high storage pressure with compliance of 5.0 mL/cmH2O. CIC management was introduced, and vibegron was initiated. After that, the urinary symptoms were resolved immediately. On video‐UDS, bladder deformity and compliance had improved. Conclusion Patients managed by spontaneous voiding should be carefully evaluated for atypical UDS findings to decide whether urological follow‐up can be considered complete.